Foundations of behavioral neuroscience - Carlson, Neil R., 1942- (Boston (Mass.) : Pearson education, 2011)
For undergraduate junior/senior level courses in Behavioral Neuroscience, Physiology of Behavior, Biopsychology, Human Neuropsychology, or Physiological Psychology. Foundations of Behavioral Neuroscience offers a briefer, sixteen chapter introduction to the foundations of physiology, incorporating the latest studies and research in the rapidly changing fields of neuroscience and physiological psychology. The text uses many human examples, case studies, and MyPsychKit (www.mypsychkit.com) featuring Carlson's Neuroscience Animations to help make the material interesting and relevant to student readers. Foundations of Behavioral Neuroscience is ideal for the instructor who wants a briefer text with a balance of human and animal cases.
Includes bibliographical references and index.
Keywords: Psychophysiology; Neuropsychiatry; Neurologie